Residential Mobility and Dental Decoration in Early Medieval Spain: Results from the Eighth Century Site of Plaza del Castillo, Pamplona - Eleanna Prevedorou; Marta Díaz-Zorita Bonilla; Alejandro Romero; Jane E. Buikstra; M. Paz de Miguel Ibáñez; Kelly J. Knudson (Dental Anthropology Association, 2010)
Excavations at Plaza del Castillo in Pamplona (northern Spain) revealed a large Islamic necropolis dating to the eighth century A.D., including the skeleton of an adult female showing intentional dental modification (PLA-159). While the practice of dental decoration was virtually absent in Medieval Spain, it is common in Africa and suggests that this individual was born in Africa and brought to Spain later in life. The historically documented occupation of Pamplona by Muslim groups from northern Africa between ca. 715 and 799 A.D. also supports an African origin. As an additional line of evidence, we investigated the geographic origins of two individuals from the cemetery, including PLA-159, via radiogenic strontium and stable oxygen isotope analyses on enamel hydroxyapatite. The human isotopic signatures were measured following established methodologies and compared to the local geochemical composition and modern precipitation values. The data analysis showed a non-local isotopic signature for both individuals, suggesting that they moved to Pamplona following childhood, probably from northern Africa, during the Islamization of the city. Stable carbon isotope analysis revealed a diet heavily based on C3 terrestrial plants. Overall, this preliminary data set exemplifies the use of biogeochemistry as an analytical tool, and provides unique insight about the diffusion of Muslim groups into the Early Medieval Iberian Peninsula.